A more-than-human life: rethinking the good life - Wich, Manda, author; Szymanski, Erika, advisor; Palmquist, Mike, committee member; Schmidt, Jenne, committee member (Colorado State University. Libraries, 2023)
Recently, within disabled discourses, there have been conversations surrounding who is considered worthy of participating in society and who is not. Additionally, those conversations have included how exhausting it can be to fight for the ability to participate in society. Lauren Berlant's concept of the good life acts as a way to understand why this feeling of exhaustion emerges in these conversations. However, it may not account for all ways of being and participating in the world. Therefore, in this thesis, I examine how a posthuman lens can help us rethink not only the broader normative ways of living a good life, but also the concept of the good life. I do this through a critical discourse analysis (CDA) of the subreddit r/disability. Additionally, I examine if the discourse of the subreddit employs good life ideals or if cripistemologies emerge in the discourse. In analyzing the subreddit, I find that that while some of the conversations reflects good life ideals and normative ways of being, other conversations challenge normative ways of being and express alternate ways of being in the world. These alternate ways of being align with the posthuman lens I employ in this thesis and allow for ways of rethinking the good life through proposing pluralistic, interdependent ways of being in the world. From the findings of this CDA of r/disability, I aim to bring attention to pluralistic, interdependent, crip ways of knowing/being that can provide alternate ways of being for both disabled and non-disabled people alike, blur the boundaries between disabled/non-disabled, and challenge those normative ways of being.
Keywords: crip theory; more-than-human; affect; posthuman; disability